Russia – Peru: History and Science Diplomacy - R. O. Reinhardt (Ибероамериканские тетради, 2022)
Thisarticle is dedicated to the200th anniversary of Peru’s independence and deals with the main milestones in evolution of Russia’s bilateral relations with this country in the context of history, foreign policy, culture and especially science. Taking into account the recently introduced new archival data, in the first part of the study, the author examines some of the circumstances of the first interstate contacts between the Russian Empire and the Republic of Peru alongside paying attention to the issues of intercultural communication. Further, applying an interdisciplinary approach, we study the period preceding the official establishment of diplomatic relations between the Soviet Union and Peru in 1969. Then, working from the premises of academic diplomacy with a focus on humanities, the author analyzes the formation and development of Peruvian studies undertaken by Russian scholars. Finally, we cast light upon the current state of affairs in Russia-Peru relations in terms of both State and public diplomacy.